A Psychological Look At The Egg Donation And The Alternative To Disclose Or Not The Story Of Conception - Albornoz Álvarez, Carla (2015)
This work is about the emotional impact in a couple who receives the chance to have a child through egg donation treatment. Many women lives a “genetic grief” before they can accept egg donation. To make a good decision it is necessary have time to think about and it's important how the women feel about this. Women who consider maternity is not only biological attachment and think that emotional attachment is the most important could accept egg donation in a good way. Also, this work explores the future consequences in family environment related to egg donation. We focus on the debate about to tell or not to tell people who were borned through egg donation. In recent years, there is more openness about this topic, even health professionals suggest to avoid maintain the secret in future and tell children about their conception.